Preservative‐free versus preserved glaucoma eye drops and occurrence of glaucoma surgery. A retrospective study based on the French national health insurance information system, 2008‐2016. Issue 7 (31st March 2020) - Chamard, Chloé; Larrieu, Sophie; Baudouin, Christophe; Bron, Alain; Villain, Max; Daien, Vincent
Abstract: Purpose: Preservatives contained in glaucoma eye drops have been shown to have a deleterious impact on the ocular surface. We aimed to assess the association between preservative exposure and the occurrence of further glaucoma surgery among patients with glaucoma or ocular hypertension in France. Methods: The study concerned all patients who first received glaucoma eye drop treatments in a French medical‐administrative database (EGB) between 2008 and 2015. Three groups were created according to the level of preservative exposure during the whole follow‐up: '0% preservatives', 'mixed' and '100% preservatives'. The occurrence of glaucoma surgery was estimated according to preservative exposure indicators in Cox multivariate models adjusted on age, sex, number of glaucoma eye drops simultaneously used, systemic antihypertensive treatment and duration of treatment. Results: The sample consisted of 12 454 patients. The median (interquartile range) follow‐up was 4.1 (1.7–6.1) years. A total of 231 (1.9%) patients underwent glaucoma surgery during follow‐up. On multivariable analysis, the risk of glaucoma surgery was increased for the 'mixed' group (hazard ratio [HR] = 3.94 [95% CI, 1.54–10.05]) and for the '100% preservative' group (HR = 7.97 [95% CI, 3.07–20.67]) when compared with the 0% preservative group. Conclusion: We found an association between exposure to glaucoma eye drop preservatives and the prevalence of further glaucoma surgery. While these data might be used to support the consideration of routine use of preservative‐free drops, in the absence of a randomized clinical trial, they cannot prove a direct cause‐and‐effect relationship between preservative‐free glaucoma eye drops and further glaucoma surgery.